Analysis of Biology Practicum Implementation in Senior High Schools in South Sulawesi - Abd Muis; Ismail Ismail; Dian Dwi Putri Ulan Sari Patongai (EduLine: Journal of Education and Learning Innovation, 2023)
Practical activities are activities that play a big role in the implementation of biology learning, because this activity will really help students improve their skills in working with nature and the environment. This research aims to find out the implementation of class XI biology practicum at SMAN in terms of conformity with the basic competencies in the 2013 curriculum. This research is descriptive research with a quantitative approach. Sampling for research subjects was carried out using cluster sampling with 10 schools as selected research subjects. The research results show that the implementation of biology practicum for class The practicum with the lowest implementation was KD 4.4 Presenting data from observations of tissue and organ structures in animals with a percentage of 37.5%, and the highest was KD 4.3 Presenting data from observations of tissue and organ structures in plants with a percentage of 85%. For the practicum implementation aspect, 30% of schools are in the very good category, 20% are in the good and sufficient category and 30% are in the very poor category..